The Effects of Personality Disorder on Auditors' Professional Skepticism - Mohsen Gholamrezaee (Shahid Bahonar University of Kerman, 2019)
Objective: This study has focused on the effects of auditors’ personality disorders on their professional skepticism. This is done in a sample of 293 auditors, consisting of chartered professional accountants, CPA, and individuals qualified for the CPA exam. Method: Data were collected applying the scrolling approach, and the statistical analysis was performed, using structural equations/regressions. The trait skepticism questionnaire of Hurtt (2010) was used to measure participants’ professional skepticism, and the brief form of the Personality Inventory for Diagnostic and Statistical Manual of Mental Disorders, fifth edition (PID-5-BF), published by APA (2013), was used to assess the personality disorder of auditors. Result: The results indicated that all the dimensions of auditors’ personality disorders affect their professional skepticism negatively. Also, the most inverse relationship can be witnessed between personality disorders and the interpersonal perception criterion for professional skepticism. Conclusion: The attention paid to the factors shaping auditors’ personality disorder and the efforts made to remove the barriers can significantly improve the level of professional skepticism.